2020
DOI: 10.2337/dc19-1975
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in Global Myocardial Glucose Metabolism in Subjects With 1-Hour Postload Hyperglycemia and Impaired Glucose Tolerance

Abstract: Impaired insulin-stimulated myocardial glucose uptake has occurred in patients with type 2 diabetes with or without coronary artery disease. Whether cardiac insulin resistance is present remains uncertain in subjects at risk for type 2 diabetes, such as individuals with impaired glucose tolerance (IGT) or those with normal glucose tolerance (NGT) and 1-h postload glucose ‡155 mg/dL during an oral glucose tolerance test (NGT 1-h high). This issue was examined in this study. RESEARCH DESIGN AND METHODS The myoca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 39 publications
3
35
0
Order By: Relevance
“…The mechanisms underlying the relationship between NAFLD and a higher myocardial oxygen consumption and a compromised ability of the LV to convert energy into stroke work have not been characterized yet. Insulin resistance is a main feature of NAFLD, and it has been found to affect myocardial metabolism [27,29,30,34] In normal conditions, 60-70% of myocardial energy is produced by fatty acid oxidation, whilst only 30-40% of energy is derived by glucose-pyruvate oxidation. There is evidence that insulin-resistant individuals have an increased oxidation of fatty acids paralleled by a decrease in glucose uptake and metabolic utilization, which results in a higher oxygen consumption and an impaired cardiac mechanical efficiency [27,29,30,34,44,45].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The mechanisms underlying the relationship between NAFLD and a higher myocardial oxygen consumption and a compromised ability of the LV to convert energy into stroke work have not been characterized yet. Insulin resistance is a main feature of NAFLD, and it has been found to affect myocardial metabolism [27,29,30,34] In normal conditions, 60-70% of myocardial energy is produced by fatty acid oxidation, whilst only 30-40% of energy is derived by glucose-pyruvate oxidation. There is evidence that insulin-resistant individuals have an increased oxidation of fatty acids paralleled by a decrease in glucose uptake and metabolic utilization, which results in a higher oxygen consumption and an impaired cardiac mechanical efficiency [27,29,30,34,44,45].…”
Section: Discussionmentioning
confidence: 99%
“…Insulin resistance is a main feature of NAFLD, and it has been found to affect myocardial metabolism [27,29,30,34] In normal conditions, 60-70% of myocardial energy is produced by fatty acid oxidation, whilst only 30-40% of energy is derived by glucose-pyruvate oxidation. There is evidence that insulin-resistant individuals have an increased oxidation of fatty acids paralleled by a decrease in glucose uptake and metabolic utilization, which results in a higher oxygen consumption and an impaired cardiac mechanical efficiency [27,29,30,34,44,45]. Recently, Mancusi et al have reported an association between a higher degree of insulin resistance estimated by HOMA-IR and a reduced MEEi [30].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A series of epidemiologic analyses from the CATAnzaro Metabolic RIsk factors (CATAMERI) study provided mechanistic insights into the association of 1-h PG with various cardiovascular risk factors. This cohort has demonstrated an association between an elevated 1-h PG in individuals with NGT and subclinical target organ damage such as carotid atherosclerosis, 162 cardiac insulin resistance, 163 fatty liver, 164,165 and impaired kidney function. 166 Similar observations were also noted in other cohort studies.…”
Section: Elevated 1-h Pg and Cardiovascular Risk Factorsmentioning
confidence: 85%